2016
DOI: 10.1002/alr.21857
|View full text |Cite
|
Sign up to set email alerts
|

The turbinal flap: an additional option for anterior skull base reconstruction. Cadaveric feasibility study and case report

Abstract: The main indication for the TF is the repair of anterior skull base defects involving the ethmoid roof. Its advantages include the double pedicle, rich vascularization, autonomy from the maxillary artery system, and preservation of the olfactory mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The mean surface area for the EEM (8.03 [1.36] cm 2 ) in the cadaveric specimen is similar to that obtained with free middle turbinate grafts, 14 but smaller than the simple (12.3 [2.3] cm 2 ) or extended (28.8 [3.3] cm 2 ) nasal floor and inferior meatus flap, as reported by Santamaria‐Gadea et al 15 However, they have the limitation of the mucosal surface necessary for the rotation of the pediculated flap.…”
Section: Discussionsupporting
confidence: 73%
“…The mean surface area for the EEM (8.03 [1.36] cm 2 ) in the cadaveric specimen is similar to that obtained with free middle turbinate grafts, 14 but smaller than the simple (12.3 [2.3] cm 2 ) or extended (28.8 [3.3] cm 2 ) nasal floor and inferior meatus flap, as reported by Santamaria‐Gadea et al 15 However, they have the limitation of the mucosal surface necessary for the rotation of the pediculated flap.…”
Section: Discussionsupporting
confidence: 73%
“…However, the safe and effective dose of fluorescence technology still needs to be further explored 39 . Many articles have evaluated the effectiveness of flap transplantation by conducting retrospective studies on wound size, degree of vascularization, surgical technique, and complications 40‐42 . In addition, studies have shown that vascularization can also promote nerve regeneration and repair, providing a healthy tissue bed for the flap 43 .…”
Section: Discussionmentioning
confidence: 99%
“…39 Many articles have evaluated the effectiveness of flap transplantation by conducting retrospective studies on wound size, degree of vascularization, surgical technique, and complications. [40][41][42] In addition, studies have shown that vascularization can also promote nerve regeneration and repair, providing a healthy tissue bed for the flap. 43 We found it interesting that in addition to the common pedicled flap, musculocutaneous flap, fascia flap, and flap, omentum flap, as a free flap, has become a valuable tool in reconstruction.…”
Section: Hotspot Analysis Of Research Pertaining To Vascularization A...mentioning
confidence: 99%
“…This flap is adequate to cover defects along the entire ethmoid roof up to a size of 8cm 2 . It can also cover the medial orbital wall and medial portion of the roof of maxillary sinus ( 38 ).…”
Section: Type Of Reconstructions In Sinonasal Tumors Surgerymentioning
confidence: 99%